Lappet-Faced Vulture, Camel and Raven of Red Sea of Egypt - Samia Ahmed Kamal (Journal of Wildlife, 2022)
Camels imported from Africa enter Egypt at Southeast borders. Movement of life animals help spreading of transboundary diseases from endemic areas to free areas. Lappet-faced vulture in Egypt territory represents highly valuable gift of nature, it is recorded in Red sea zone of Egypt. Their numbers indicate vulture breeding rate was promising for such endangered species. The Egyptian authority played a great role in protecting this land from destructive behavior against wild life. The raven accompany lappet-faced vulture, while eating together, which indicates healthy atmosphere at their habitat. This work performed while studying the epidemiology of this region and the impact of movements of live animals coming from Africa on trans-boundary diseases. Lappet-faced vultures and Raven play major role in preventing transmission of infectious agents from camel carcasses. However, Vulture has strong digestive system that kill a wide range of harmful microorganisms. Moreover, these scavenge birds are considered dead end hosts for these diseases. The study provides vivid proof of the innate intelligence that distinguishes the raven, as well as evidence that the black bird possesses a common language among themselves and between them and the Lappet-faced vulture. Lappet-faced vulture is usually nesting at acacia trees & mountains. However some acacia trees showed defected growth as a result of the strong wind, such observation is of great importance to understand geography of such habitat. Lappet-faced vulture is endangered species and need more attention and care.
Keywords: Lappet-faced vulture